2010
DOI: 10.1016/j.cub.2010.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Visual Control of Altitude in Flying Drosophila

Abstract: Unlike creatures that walk, flying animals need to control their horizontal motion as well as their height above the ground. Research on insects, the first animals to evolve flight, has revealed several visual reflexes that are used to govern horizontal course. For example, insects orient toward prominent vertical features in their environment [1-5] and generate compensatory reactions to both rotations [6, 7] and translations [1, 8-11] of the visual world. Insects also avoid impending collisions by veering awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 42 publications
2
69
0
Order By: Relevance
“…All experiments were performed in a 150 cm × 30 cm × 30 cm wind tunnel (27,28) equipped with a visual projection system (Fig. 1A).…”
Section: Methodsmentioning
confidence: 99%
“…All experiments were performed in a 150 cm × 30 cm × 30 cm wind tunnel (27,28) equipped with a visual projection system (Fig. 1A).…”
Section: Methodsmentioning
confidence: 99%
“…To safely fly in cluttered environments, insects instead rely on image motion, also known as optic flow 38,39 , generated by their own displacement relative to the surroundings 40 . It has been experimentally shown that their neural system reacts to optic flow patterns 41,42 to produce a large variety of flight capabilities, such as obstacle avoidance 40,43 , speed maintenance 44 , odometry estimation 45 , wall following and corridor centring 46 , altitude regulation 47,48 , orientation control 49 and landing 50,51 . Optic flow intensity is proportional to the distance from objects only during translational movements, but not during rotational movements when it is proportional to the rotational velocity of the agent.…”
Section: Review Insightmentioning
confidence: 99%
“…Real-time tracking is performed as images are acquired, removing the need for storing large amounts of digital information [17][18][19] and allowing researchers to influence the animal's environment in real time through virtual reality, robotics, or other dynamical stimulus regimes [22][23][24]. Even under controlled laboratory conditions with small numbers of individuals, automated image-based tracking is a difficult computer vision problem.…”
Section: Automated Image-based Trackingmentioning
confidence: 99%